A novel culture device for the evaluation of three-dimensional extracellular matrix materials - Akhyari, Payam; Ziegler, Heiko; Mambou Kamdem Gwanmesia, Patricia Neh; Schilp, Sören; Aubin, Stefanie (Journal of tissue engineering and regenerative medicine, 2014)
Cell-matrix interactions in a three-dimensional (3D) extracellular matrix (ECM) are of fundamental importance in living tissue, and their in vitro reconstruction in bioartificial structures represents a core target of contemporary tissue engineering concepts. For a detailed analysis of cell-matrix interaction under highly controlled conditions, we developed a novel ECM evaluation culture device (EECD) that allows for a precisely defined surface-seeding of 3D ECM scaffolds, irrespective of their natural geometry. The effectiveness of EECD was evaluated in the context of heart valve tissue engineering. Detergent decellularized pulmonary cusps were mounted in EECD and seeded with endothelial cells (ECs) to study EC adhesion, morphology and function on a 3D ECM after 3, 24, 48 and 96 h. Standard EC monolayers served as controls. Exclusive top-surface-seeding of 3D ECM by viable ECs was demonstrated by laser scanning microscopy (LSM), resulting in a confluent re-endothelialization of the ECM after 96 h. Cell viability and protein expression, as demonstrated by MTS assay and western blot analysis (endothelial nitric oxide synthase, von Willebrand factor), were preserved at maintained levels over time. In conclusion, EECD proves as a highly effective system for a controlled repopulation and in vitro analysis of cell-ECM interactions in 3D ECM.